Análise harmônica aplicada a dados mensais de chuva para o município de Belém - RIBEIRO, Angelo Rodrigo Brito (2020)
This paper describes a research on the behavior of rainfall accumulated in the city of Belém-PA and a way to model the discrete data observed in an equation from the Fourier Series, considering the major problem that is shown in climate modeling where only data discrete precipitation is measured for use in weather forecasting. Assuming that the rainfall regime in the Amazon region is well defined in the rainy and less rainy periods, emphasis was given to verifying whether the methods used to model the meteorological data in an equation and then a representative graph of precipitation behavior over throughout the year, as was obtained in other regions of the country. The paper seeks to show the need for meteorological models to forecast the climatic conditions in the region, using rainfall data from 1987 to 2016, in order to help the regional population change that are occurring